(untitled) (Research, Society and Development, 2024)
There has never been as much access to technology as there is today. The generation we now refer to as young adults has grown up surrounded by digital media, witnessing the emergence and expansion of the internet. An abundance of content is made available daily, both to please its users and to capture their attention. Faced with this landscape, a decision was made to investigate the subjective and social influences of digital media consumption on young academics and its impacts on their education. To this end, a qualitative-quantitative and exploratory study was conducted through a questionnaire hosted on the Google Forms platform. The questionnaire, consisting of both open-ended and closed-ended questions, was accessed by 36 respondents university students aged between 18 and 28 years old. The analysis of the collected information was conducted through mixed content analysis, leading to the establishment of two categories a posteriori: "university students and the consumption of digital media" and "the effect of media on the subjective dimension and education.". The current study emphasized the complex relationship between young individuals and the consumption of digital content, characterized as excessive and often associated with positive feelings such as relaxation and entertainment. However, it is crucial to note that prolonged use can trigger negative emotions like irritation and guilt, highlighting the impact of these interactions on how these young individuals approach their academic progress and personal development.